Management - Griffin, Ricky W. (Boston, MA Cengage, 2022)
"Master the process of management with the skills-based, functional approach in Griffin’s MANAGEMENT, 13E. Timely content focuses on active planning, leading, organizing and controlling as you examine emerging management topics. New discussions explore the impact of technology, the importance of a green business environment, the need to adapt in changing times, ethical challenges and the role of diversity. This is one of the first management books to examine the impact of the COVID-19 pandemic and its resulting economic turmoil. New cases and updated learning features support an effective balance of classic theory and contemporary practice. Hundreds of current examples highlight organizations such as Starbucks, Hilton Hotels, Quicken Loans and Honey Pot. New MindTap digital resources further guide you in thinking and acting like a successful manager with learning, application and study modules for each chapter. Immediate feedback and links to the printed book help you prepare for exams." --
Cover Page
Title Page
Copyright Page
Dedication
Preface
Acknowledgments
Part 1. Introducing Management
Chapter 1. Managing and the Manager’s Job
1-1. An Introduction to Management
1-2. The Management Process (What do Managers do?)
1-2a. Planning and Decision Making: Determining Courses of Action
1-2b. Organizing: Coordinating Activities and Resources
1-2c. Leading: Motivating and Managing People
1-2d. Controlling: Monitoring and Evaluating Activities
1-3. Kinds of Managers
1-3a. Managing at Different Levels of the Organization
1-3b. Managing in Different Areas of the Organization
1-4. Basic Managerial Roles and Skills
1-4a. Managerial Roles
1-4b. Managerial Skills
1-5. The Nature of Managerial Work
1-5a. The Science and the Art of Management
1-5b. Becoming a Manager
1-5c. The Scope of Management
Includes bibliographical references and index.
Keywords: Management